Case report of rare tissue injury and left arm dislocation after incorrect blood pressure measurement during clinical practice - Karaman, Özen Esra; Altıparmak, Yüksel Duygu (The European Research Journal, 2023)
In midwifery education based on theoretical and practical foundations, students encounter midwifery profession education which based on for the first time in the Basic Clinical Skills in Midwifery Course. The aim of the Basic Clinical Skills in Midwifery Course is to help students understand the basic philosophy of midwifery and the role of the midwife in the health system, and to provide the student with knowledge, skills and attitudes about the basic concepts, principles and methods in midwifery care. In the Basic Clinical Skills in Midwifery Course, students are offered learning methods that will enable them to develop behaviors in the cognitive, affective and psychomotor domains. In this context, the course is carried out in skill development laboratories and clinical environments, after the lecturer in the classroom explains the basic concepts, the health system and midwifery, the protection and development of health, the fulfillment of physiological care needs, and the demonstration of the skills related to the psychomotor domain. Clinical practices are an indispensable element of midwifery education. The Midwifery Basic Clinical Skills Course has a very important place in clinical skills training, as students experience the hospital environment for the first time in their education life and experience midwifery practices for the first time on real patients. The aim here is to discuss a case that can be experienced after the correct application of vital sign measurement techniques and erroneous measurement.